Parameters optimization of heat treatment for obtaining luminescent PZT powders - Silva, Margarete Soares da; Cavalheiro, Alberto Adriano; Zaghete, Maria Aparecida [UNESP]; Cilense, Mário [UNESP]; Teixeira, Guilhermina Ferreira [UNESP]; Cavenago, Gustavo F.; Dias, Rafael Gomes; Silva, Lucas L. (Trans Tech Publications, 2014)
Low crystalline PZT powder samples were successfully synthesized using polymeric precursor method and slow decomposition steps. The polymeric resin precursor was thermal treated in a muffle type oven varying the temperature from 250 °C to 700 °C and the time from 3 to 24 hours in order to investigate the order/disorder mechanism toward the amorphous powders. Powder samples with low crystalline phases were obtained at lower temperatures and long time of thermal treatment, demonstrating a kinetic dependence for organic removal and a thermodynamic barrier for crystallization processes. Through XRD and FTIR spectroscopy characterizations the long time thermal treated samples showed to be composed of the solid solution of metal oxides in absent of organic matter, originating broad XRD peaks profiles and no carbonaceous bands in FTIR spectra. A Photoluminescence characterization showed that the peak emission is higher for disordered and homogeneous phases, which only can be reached through the long time of thermal treatment.
Keywords: pzt poder; Ceramic; photoluminescence; Thermal Treatment